Incidencia de los sistemas de control en la captación de capital humano - Giraldo Vélez, Olga Lucía; Herrera Suescún, Lizeth Andrea (Revista de Ingeniería, 2001)
The results obtained about how technology enterprises in Colombia are handling their Human Resources, how it is view by their employees and the benefits of both are presented. The labor force matrix is built over the matrix of Capitalization of Human Talent in relation with Control Methods, leading the Personal Change Patherns/Enterprise Qualification (PCP/CE). After that, hypothesis on the behavior of enterprises and employees is obtained. Finally, the results of the studie are presented, and eventhough they have a lack of value given the size of the population tested, they do confirm the good sense of the hypothesis.